2022
DOI: 10.3389/fonc.2022.811716
|View full text |Cite
|
Sign up to set email alerts
|

Antitumorigenic Effect of Tramadol and Synergistic Effect With Doxorubicin in Human Breast Cancer Cells

Abstract: BackgroundBreast cancer in women is one of the leading causes of cancer mortality worldwide, and curative therapy is the main focus of clinical treatment. Anesthetic-analgesic techniques might alter stress responses and immunity and thereby influence outcomes in cancer patients. This study investigated the effect of tramadol on breast cancer progression and metastasis.MethodsThe effects of tramadol on two different subtypes of human breast adenocarcinoma cell lines, MDA-MB-231 and MCF-7, were studied with rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Exercise [107,108] Stress [4,7,[108][109][110][111] Meditation [111][112][113] Gut microbiota [114,115] Smoking [53][54][55][56] On the other hand, the opioid analgesic tramadol could inhibit proliferation, migration, and invasion of breast cancers by inactivating the α2-adrenoceptor signaling pathway [50]. Based on cellular experiments, Huang et al concluded that tramadol inhibits the progression of breast cancer cells and should be investigated further for use in combination therapy, especially for triple-negative breast cancer [51]. Like tramadol, the α2-adrenoceptor antagonist rauwolscine also suppressed tumor growth, in mice with human breast cancer cells [52].…”
Section: Topic Referencesmentioning
confidence: 99%
“…Exercise [107,108] Stress [4,7,[108][109][110][111] Meditation [111][112][113] Gut microbiota [114,115] Smoking [53][54][55][56] On the other hand, the opioid analgesic tramadol could inhibit proliferation, migration, and invasion of breast cancers by inactivating the α2-adrenoceptor signaling pathway [50]. Based on cellular experiments, Huang et al concluded that tramadol inhibits the progression of breast cancer cells and should be investigated further for use in combination therapy, especially for triple-negative breast cancer [51]. Like tramadol, the α2-adrenoceptor antagonist rauwolscine also suppressed tumor growth, in mice with human breast cancer cells [52].…”
Section: Topic Referencesmentioning
confidence: 99%
“…98 The biofilm composite nano-drug delivery system (OMVs-MSN-5-FU) has also been confirmed to have good anti-tumor effect in lymph node metastasis from oral squamous cell carcinoma. 99 In a recent study, BEVs were used to co-load paclitaxel (PTX) and regulate the expression of DNA damage response 1 (Redd1)-siRNA, thereby suppressing tumor growth and modulating the tumor metabolism microenvironment. The siRNA@M-/PTX-CA-OMVs developed in this study were able to release PTX in response to the acidic tumor microenvironment (pH 6.8) in a triplenegative breast cancer model.…”
Section: Engineered Bevsmentioning
confidence: 99%
“…Affected by DOX‐OMVs, macrophages are recruited in the tumor microenvironment and perform a synergistic antitumor effect with the OMVs 98 . The biofilm composite nano‐drug delivery system (OMVs‐MSN‐5‐FU) has also been confirmed to have good anti‐tumor effect in lymph node metastasis from oral squamous cell carcinoma 99 . In a recent study, BEVs were used to co‐load paclitaxel (PTX) and regulate the expression of DNA damage response 1 (Redd1)‐siRNA, thereby suppressing tumor growth and modulating the tumor metabolism microenvironment.…”
Section: The Potential Of Bevs In Clinical Applicationmentioning
confidence: 99%
“…In a xenograft mouse model, Kim et al showed that a clinical dose of tramadol had antitumor effects on MCF-7-cell-derived breast cancer [ 171 ]. In addition, tramadol may regulate EMT and exert cytotoxic effects in breast cancer cells [ 172 ]. However, literature on tramadol in PC progression is lacking, and further laboratory studies are required.…”
Section: The Effects Of Anesthetics On Pc Progression: From Laborator...mentioning
confidence: 99%